Surface Treatment of Rammed Earth Heritage Sites Using MICP Technology: An Investigation of Rainwater Erosion Resistance via Indoor Experiments and In Situ Testing - Liang Liu; Yun Zhang; Wanting Chen; Haiying Cao; Lianjun Guo; Lingling Zheng; Tianli Li; Rong Shu; Dongdong Li (Geofluids)
Rammed earth, a commonly used building material in ancient times, differs from natural sedimentary layers in that it is more compact. Buildings constructed from historical rammed earth sites frequently encounter the issue of rainwater erosion. Microbially induced calcium carbonate precipitation (MICP) is commonly applied to sand soil treatment, yet reports on its use for stabilizing rammed earth are scarce. This study focused on the rammed earth of the Shanhaiguan Great Wall and explored the efficacy of MICP in mitigating rain erosion through permeation tests, splash experiments, and scouring trials. The findings indicate that the forms of rain erosion damage under MICP treatment vary across different operational conditions. In laboratory experiments, as the concentration of the cementation solution increases, the amount of calcium carbonate crystals also increases. However, the permeability, splash resistance, and rain erosion resistance initially increase and then decrease. When the cementation solution concentration is 1.0 mol/L, the penetration rate is the highest, lasting 712.55 s. The splash pit rate is the lowest, at only 1.2 mm, and the soil erosion rate is the lowest, at only 4.13%. The rain erosion resistance in the field test exhibit the same trend, and the optimal concentration is 1.2 mol/L. The optimal concentration mechanism involves the aggregation of calcium carbonate crystals at suitable cementation solution concentrations, which begin to fill the soil particle pores, effectively resisting rainwater erosion. At lower concentrations of the cementation solution, calcium carbonate crystals are merely adsorbed by soil particles without blocking the pores. Due to the high compressibility of rammed earth, which results in lower porosity, a higher concentration of the cementation solution leads to rapid pore clogging by excessive calcium carbonate crystals, which accumulate on the surface to form a white crust layer. The MICP technique can effectively alleviate rainwater erosion in rammed earth, and the optimal concentration needs to be tailored to the porosity of the rammed earth. This mechanism was also validated in field scouring experiments on the Shanhaiguan Great Wall’s rammed earth.